The Stability and Failure of Deep Underground Structures at Potash Mining Deposits - Yiqiang Zhang; Siarhei Lapatsin; Michael Zhuravkov; Guangbin Yu; Ivan Karpovich (Applied Sciences)
The article describes the peculiarities of strength and stability evaluation for deep geotechnical structures located in salt rock masses at great depths. A number of numerical studies are presented for the deep mining excavations of various cross-sections. The numerical simulations are conducted using a specific coupled algorithm of the finite element method (FEM) and distinct element method (DEM), which allows not only the prediction of dangerous zones in the undermined rock mass but also to simulation of the block fracture of the rock mass directly. Potential critical zones in the rock mass are established using an original complex limit state criterion for rock masses and FEM simulation results. Mentioned original criterion is a specific multicriterial method, which considers potential tensile, compressive and shear failure as well as crack propagation. To define the block-structure formulation in the rock mass it is proposed to use the Lade criterion in the complex limit state zones. Furthermore, block-structured rock mass behavior is simulated using DEM to predict its block-like fracture. The results of numerical studies clearly show that the mechanical behavior of potash salt rock masses significantly differ at moderate and great mining depths. Namely, the volume of the limit state zones nonlinearly increases with the increase in the mining depths up to double the size of the excavation cross-section. However, the exact amount of potentially failed rock mass has to be established using the direct DEM simulation in the limit state zones.